Complete plastid genome of Gracilaria bailiniae (Rhodophyta) and phylogenetic analysis. Issue 1 (2nd January 2019) - Liu, Tao; Yang, Shouguo; Wu, Xiangyu; Chen, Wei Zhou; Zhang, Jing; Tang, Xianming
Abstract: The complete Gracilaria bailiniae plastid genome was determined and analyzed in this work. It had a circular mapping molecular with the length of 185, 129 bp and contained 231 genes including 193 protein-coding, 3 rRNA, 1 tmRNA, 29 tRNA genes, and 5 unidentified open reading frames. Phylogenetic analysis showed that G. bailiniae clustered together with Gracilaria chorda and Gracilariopsis lemaneiformis . The complete plastid genome provided in this work would be useful for elucidation of Gracilaria evolution.